The Use of 'Etic' to Solve Communication Barrier between the Supervisor and the Student in Social Media Era - Jatmika, Surya (Universitas Muhammadiyah Surakarta, 2017)
Previous studies reported findings that indicate drawbacks linked to the long-term completion of the final assignment at various universities in Indonesia. One of the major findings of these studies revealed that the communication problem between students and supervisors is the main obstacle in the completion of their final assignment. Based on the assessment and observation at the level of Bachelor’s degree (S1) and magister program (S2), it can be assumed that a high number of lecturers/supervisors incline to allocate less special time for guiding their students. They commonly give various reasons and indecisive time for guidance. The reason such as the lecturers’ reluctance to supervise students in relation to their less interest of student’s final paper topics, dislike of the student’s personality, absence of consultation schedule without obvious reason, and being emotional in supervising the students’ writing. In the contemporary era, communication is dominated by the individual use of social media. Each individual must always be connected with Smartphone, including lecturers and students. In addition, it also affects the communication pattern of lecturers and students. This research is a literature study using qualitative approach. It was done by examining and analyzing the prevailing problems based on the existing literature. Based on the analysis, it can be concluded that code of ethics is needed as solution to overcome the problems of communication between student and supervisor. It formulates code of ethics named the “ETIC